Impact of Puccinia punctiformis on Cirsium arvense performance in a simulated crop sequence - Chichinsky, Daniel; Larson, Christian; Eberly, Jed; Menalled, Fabian D.; Seipel, Tim (Frontiers in Agronomy, 2023)
Cirsium arvense (Canada thistle) is a perennial weed that causes significant economic losses in agriculture. An extensive rhizomatous root system makes C. arvense difficult to manage, particularly in agricultural systems that use tillage as a primary management tool. There is a need for the development of integrated weed management toolsets that include C. arvense biological controls. Puccinia punctiformis (thistle rust) is an autoecious fungal pathogen that systemically infects C. arvense, with the potential to reduce host vigor over time. The goal of this study was to integrate the P. punctiformis biocontrol with a simulated annual cropping sequence in a greenhouse environment and evaluate C. arvense’s above-and belowground biomass production, and its competitive ability. Repeated P. punctiformis inoculations produced systemically infected C. arvense stems in greenhouse pots over time. Cirsium arvense that was inoculated with P. punctiformis had 1.6 grams/pot (p = 0.0019) less aboveground biomass and 5.6 grams/pot (p < 0.001) less belowground biomass, compared to the non-inoculated (control). Puccinia punctiformis and crop competition interacted additively to lower aboveground (p<0.001) and belowground (p<0.001) C. arvense biomass more than individual use of either the biocontrol or competition alone. The aboveground competition intensity of C. arvense in a mixed crop sequence, relative to non-inoculated C. arvense grown in a monoculture, was moderately impacted by the P. punctiformis biocontrol (p = 0.0987). These results indicate that systemic infection can affect biomass production and reduce the competitive ability of C. arvense. Overall, P. punctiformis can be integrated into competitive annual cropping sequences with the potential to reduce C. arvense vigor over time.